2003
DOI: 10.1128/aem.69.9.5364-5371.2003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Host Range, and Genetic Characterization of Two Coliphages

Abstract: Two coliphages, AR1 and LG1, were characterized based on their morphological, host range, and genetic properties. Transmission electron microscopy showed that both phages belonged to the Myoviridae; phage particles of LG1 were smaller than those of AR1 and had an isometric head 68 nm in diameter and a complex contractile tail 111 nm in length. Transmission electron micrographs of AR1 showed phage particles consisting of an elongated isometric head of 103 by 74 nm and a complex contractile tail 116 nm in length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 35 publications
2
64
0
2
Order By: Relevance
“…This cocktail inclusion selection criterion, for example, would exclude phages such as AR1, which infects broadly across the STEC strains but also infects 53% of the ECOR strains and, to a lesser degree, LG1 (16 of 72 ECOR; 22%). 59 This need for selectivity is compounded once we consider the use of multiple phages in a cocktail. When one considers the need to produce large quantities of phage for commercial application, CEV2 would also appear appropriate, efficiently infecting and generating high-yield stocks in TSB on the sequenced lab strains B and W3110 (both safety class 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cocktail inclusion selection criterion, for example, would exclude phages such as AR1, which infects broadly across the STEC strains but also infects 53% of the ECOR strains and, to a lesser degree, LG1 (16 of 72 ECOR; 22%). 59 This need for selectivity is compounded once we consider the use of multiple phages in a cocktail. When one considers the need to produce large quantities of phage for commercial application, CEV2 would also appear appropriate, efficiently infecting and generating high-yield stocks in TSB on the sequenced lab strains B and W3110 (both safety class 1).…”
Section: Discussionmentioning
confidence: 99%
“…long ago by phage researchers and has also been central in the clinical use of antibiotics, but seems to be overlooked by some in the design of phage cocktails during the recent resurgence in phage therapy. 24,59,[61][62][63] When E. coli O157:H7 NCTC 12900 is infected with CEV2 alone ( fig. 3a and B), the phage rapidly adsorb and largely kill the host, both aerobically and anaerobically, but mutant bacteria soon re-grow.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some coliphages use this strategy naturally: phage Mu inverts the orientation of the receptorinteracting gene by a phage-encoded recombinase (Kamp et al, 1978), and Scholl et al (2001) described a coliphage possessing two different tail fibre proteins that showed the combined host range of phages containing one or the other protein. About 30 different O serotypes must be lysed to cover the majority of EPEC and ETEC strains worldwide (Robins-Browne, 1987;Goodridge et al, 2003). Cocktails of several phages will be necessary to get sufficient breadth of host range and to reduce the probability of resistance developing.…”
Section: Why E Coli?mentioning
confidence: 99%
“…The viral particle contains an isometric head and a contractile tail of 103 by 74 and 116 by 16 nm, respectively (17). It has a typical T4-like virion morphology under a transmission electron microscope.…”
mentioning
confidence: 99%